2010
DOI: 10.5206/cjsotl-rcacea.2010.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Applied Methods of Teaching about Oppression and Diversity to Graduate Social Work Students: A Case Example of Digital Stories

Abstract: Social work education accreditation requires the completion of course work specifically around issues related to oppression and diversity within society. Educators offer a range of approaches to engage students in discussion about oppression and diversity from academic content and structured curriculum to reflective practice and experiential learning opportunities. The following describes a Master of Social Work course on oppression, social justice, and diversity offered at a western Canadian university that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, our current knowledge of creating socially just and inclusive educators through academic courses is restricted to traditional face-to-face course delivery. Some extant research from sociology and healthcare has examined pedagogical approaches to teaching diversity courses online (Littlefield and Berterra, 2004; Merryfield, 2001; Walsh et al , 2010), but no studies we know of examine this issue for graduate preparation programs in education.…”
mentioning
confidence: 99%
“…However, our current knowledge of creating socially just and inclusive educators through academic courses is restricted to traditional face-to-face course delivery. Some extant research from sociology and healthcare has examined pedagogical approaches to teaching diversity courses online (Littlefield and Berterra, 2004; Merryfield, 2001; Walsh et al , 2010), but no studies we know of examine this issue for graduate preparation programs in education.…”
mentioning
confidence: 99%
“…Student Group Work and Presentation using Various Pedagogical Tools. Four studies (11%) discussed the use of student group work and presentation to engage students in learning social justice issues (Littlefield & Roberson, 2005;Nicotera & Walls, 2010;Rosen et al, 2017;Walsh, Shier, Sitter, & Sieppert, 2010). Digital storytelling blends creative writing, oral history, and art therapy into a first-person narrative video to foster community participation, collaboration, professional development, and participatory research.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Another five studies invited community-based guest speakers to their classes (e.g., community members or social workers) as a teaching method or teaching project (Chonody et al, 2009;Nordberg et al, 2017;Ostrander, Lane, McClendon, Hayes, & Smith, 2017;Wagaman et al, 2019;Walsh et al, 2010). For instance, in a political social work training project, political social workers with experience of running political campaigns were invited as guest speakers to lead training modules in two schools of social work (Ostrander et al, 2017).…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Globerman and Chan (2000) advocated for weekly brief lectures on appraisal questions, topics, and references, and small group and full class review discussions, culminating in an article review assignment. Other suggestions included involving students in an ongoing research program in the faculty (Cameron & Este, 2008), using agency staff as a co-instructors, directing students to carry out a research project on an actual agency issue (Knee, 2002;Wainstock, 1994), or integrating research within field placements and having practicum supervisors visit classrooms to discuss issues they have researched or would like to research and invite student participation (Cameron & Este, 2008;Walsh, Shier, Sitter, & Sieppert, 2010). Montcalm (1999) found that engaging students in agency-based research allows students to understand how the outcomes of their research can influence practice, policy and program change and Machtmes (2009) proposed service-learning approaches.…”
Section: Introductionmentioning
confidence: 99%